Molecular Dynamics Simulation of HIV Fusion Inhibitor T-1249: Insights on Peptide-Lipid Interaction - Martins do Canto, António Manuel Teixeira (2013)
T-1249 is a peptide that inhibits the fusion of HIV envelope with the target cell membrane. Recent results indicate that T-1249, as in the case of related inhibitor peptide T-20 (enfuvirtide), interacts with membranes, more extensively in the bilayer liquid disordered phase than in the liquid ordered state, which could be linked to its effectiveness. Extensive molecular dynamics simulations (100 ns) were carried out to investigate the interaction between T-1249 and bilayers of 1-palmitoyl-2-oleoyl-phosphatidylcholine (POPC) and POPC/cholesterol (1:1). It was observed that T-1249 interacts to different extents with both membrane systems and that peptide interaction with the bilayer surface has a local effect on membrane structure. Formation of hydrogen bonding between certain peptide residues and several acceptor and donor groups in the bilayer molecules was observed. T-1249 showed higher extent of interaction with bilayers when compared to T-20. This is most notable in POPC/Chol membranes, owing to more peptide residues acting as H bond donors and acceptors between the peptide and the bilayer lipids, including H-bonds formed with cholesterol. This behavior is at variance with that of T-20, which forms no H bonds with cholesterol. This higher ability to interact with membranes is probably correlated with its higher inhibitory efficiency.